2015
DOI: 10.1080/23311932.2015.1018696
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, encapsulation, and health benefits of β-carotene - A review

Abstract: β-carotene is a principle carotenoid in carrots, and of the most common and widely studied carotenoids. Carotenoids are the phytonutrients that impart a distinctive yellow, orange, and red color to various fruits and vegetables. β-carotene is important not only for the color that it imparts to the food stuffs, but also because of the myriad of associated health benefits. It is the most potent precursor of vitamin A and is present naturally as a mixture of various isomers (cis and trans) of β-carotene molecule.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
119
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 78 publications
(84 reference statements)
1
119
0
12
Order By: Relevance
“…Both the carotenes are very high in OFSP compared to the common consuming yellow to orange vegetables and fruits. As reported by theGul et al (2015) the carotenoid concentration in different foods, such as carrot (43.5-88.4 µg/g), mango (10.9-12.1 µg/g), and tomato (2.17-2.83 µg/g), contain the lower concentration of the BC than the OFSP. In case of the total carotenoids, 570 µg/g (db) of the carotenoids are reported byKim et al (2015) in OFSP from Korea.…”
mentioning
confidence: 76%
“…Both the carotenes are very high in OFSP compared to the common consuming yellow to orange vegetables and fruits. As reported by theGul et al (2015) the carotenoid concentration in different foods, such as carrot (43.5-88.4 µg/g), mango (10.9-12.1 µg/g), and tomato (2.17-2.83 µg/g), contain the lower concentration of the BC than the OFSP. In case of the total carotenoids, 570 µg/g (db) of the carotenoids are reported byKim et al (2015) in OFSP from Korea.…”
mentioning
confidence: 76%
“…β-carotene is an orange colored compound belonging to the carotenoid family that can be found in many fruits and vegetables, including pumpkins, mangoes, tomatoes, carrots, and spinach (Durante, Lenucci, D'Amico, Piro, & Mita, 2014;Gul, Tak, Singh, Singh, Yousuf, & Wani, 2015). Consumption of this carotenoid is important for maintaining human health and wellbeing because it is enzymatically converted to retinol (vitamin A) in the human intestine by the β-carotene 15,15'-monoxygenase thus constituting the most common and safe source of vitamin A (Álvarez, Vaz, Gronemeyer, & de Lera, 2014;Haskell, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative study of phytoconstituents in the selected active extracts using GC-MS revealed a wide range of bioactive constituents (Figures 4-9) that have dynamic therapeutic properties (e.g., antioxidant and anticancer). The major form of carotenoids present in date fruit was β-carotene (Figure 4), which has been reported to have antioxidant activity in vitro and in vivo [22,23]. In a recent study, the ethanol extract of the fig reduced the viability of HeLa cells and had an IC 50 value of 12 µg/mL [24].…”
Section: Discussionmentioning
confidence: 99%